Multi-Scale Decay Mechanism of Emulsified Asphalt Cold Recycled Mixture Under Freeze-Thaw - Yanhai Yang; Liang Yue; Ye Yang; Guanliang Chen (The Baltic Journal of Road and Bridge Engineering)
The road performance decay law of EACRM under freeze-thaw cycles was studied using laboratory tests on the macroscopic scale in order to comprehensively analyze the serious performance damage mechanism of emulsified asphalt cold recycled mixture (EACRM) in cold regions during the service period. The surface cracking behavior, internal void evolution characteristics, and asphalt mortar morphology damage of EACRM under freeze-thaw cycles were studied by means of digital speckle, industrial CT, and scanning electron microscope (SEM) on the mesoscopic and microscopic scale. The results show that along with the increase in the number of freeze-thaw cycles, the road performance of EACRM decreases significantly. The surface of EACRM obviously cracks, and the width and number of main cracks increase significantly. The fatigue times of the maximum horizontal strain in the whole field gradually decrease. Air voids and the average volume of meso-void visibly increase. The microcracks of cement-emulsified asphalt mortar constantly emerge at the interface. The serious damage of the “three-dimensional network structure” is the fundamental reason for the performance decay of EACRM in cold regions. The performance damage of EACRM in cold regions is aggravated by water seeping into voids from cracks. Eventually, EACRM shows serious freeze-thaw inflicted damage.